The relationship between school districts and parental commuting behavior: Analysis of gender differences in the Chinese context - Jiang, Huaxiong; Liu, Qingfang; Li, Yongling; Guo, Kaifei; Guo, Yuanyuan (Frontiers in Environmental Science, 2022)
The distribution of school districts would largely influence people’s commuting distance, but this association is hardly examined. This study applies the 2015 Xiamen household travel survey to investigate the associations between the school district and parental commuting behavior. The results showed that school districts mainly affect the parents’ commuting distance when the interaction effects between gender and commuting distance are considered. Specifically, the school district is positively associated with commuting distances for males, whereas the opposite trend is observed for females. Then, variations exist in the effects of the school district on parental commuting distance between respondents with different levels of education. The school district quality is positively associated with the commuting distance for respondents without college degrees, especially male respondents, whereas no significant association was found for more respondents with college degrees. Male respondents, especially those without college degrees, suffer higher costs and longer commuting distances than their female counterparts. This study highlights that urban planners and policy makers should consider the impact of school districts and rethink the most effective distribution of high-quality primary schools to reduce socio-spatial inequality (e.g., disadvantage of males in commuting).